Performance of multi-relay cooperative communication using decode and forward protocol - . Nasaruddin; . Mayliana; . Roslidar (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Nowadays, the development of wireless communication systems will be refer to user cooperative communication system in which a source information can transmit data to a destination through a relay. This can reduce the effect of fading on wireless communication channel which is a major problem in wireless communication system that can degrade the system performance. In this paper, we investigate the performance of multi-relay cooperative communication using decode and forward protocol in terms of channel capacity, bit error rate (BER) and throughput.  The use of decode and forward protocol in multi-relay cooperative communication offers cooperation among users to generate virtual multiple antennas to increase the channel capacity and also can give better system performance. Furthermore, the simulation model of the system and computer simulation is developed to evaluate the performance of multi-relay cooperative communication. The simulation result shows that the channel capacity increases as the value of signal to noise ratio (SNR) increases. Also, the channel capacity increases as the number of relays increases. Moreover, the performance of multi-relay cooperative communication performs better than a single-relay cooperative communication by using decode and forward protocol in terms of BER. Furthermore, multi-relay cooperative communication provides a good throughput of the system compared to a single-relay. Therefore,  the multi-relay cooperative communication is useful to mitigate the effects of channel fading, increase the channel capacity, improve the system performance and provide a good throughput by exploiting decode and forward protocol.